Design and Implementation of a Real-Time Automated ECG Diagnosis (AED) System (Global Journals of Research in Engineering, 2013)
Automated ECG diagnosis (AED)
Keywords: AED system; ECG; feature extraction; heart beat detection; P-QRS-T wave; wavelet transform